Iraqi Propolis effective in avoiding deviations of gut rat's homeostasis exposed to AFB-1 - Alqayim, Majida A.J.; Shehab, Ahmed Ayed (Journal of Kerbala for Agricultural Sciences, 2017)
Background: Consumption of food contaminated with Aflatoxin-B1(AF-B1), caused deleterious effects on different body’s systems ,specially GIT in direct and indirect manners. To investigate the protective role of propolis against AF-B1 effects on rats gut, 24 male rats divided into equal 4 groups: group (C )was control, second group (AF) received Aflatoxin-B1 ( 0.025mg/kg ), third group( P) received Propolis in dose (50 mg /kg BW) and the fourth group( AFP) received Aflatoxin-B1 (0.025 mg/ 1kg BW) + Propolis (50 mg / 1kg BW).after 60 days of experiment , intestinal D-zylose adsorption and histomorphological changes were measured Results: Results revealed that intestinal absorption function of D-Xylose sugar was reduced in AFB-1 exposed rats , meanwhile Propolis improve D-xylose absorption in rats exposed to the AFB-1. Histomorphological measurements include mucosa thickness, Villus high, Crypts depth, Villus/crypt ratio, and goblet cells density in the three portions of small intestine decreased significantly in AF group and increased significantly in P group and kept semi-normal in AFP group in comparison with the control group. Analysis of light microscopic photograph revealed that administration of aflatoxin-B1 cause deleterious changes in stomach, and intestinal tissues, while Propolis was efficient in improving these changes to normal condition. Conclusions: Intestinal absorptive function and histomorphological measurements were altered by Aflatoxin-B1, and the duodenum was the most affected part from the intestine. Results of propolis showed a high activity to improve all the above measurements and counter the deleterious effect of Aflatoxin-B1 to normal situation.